A peep into information and technology - Chandra Shekhar, G; Arathi, Ch (Recent Research in Science and Technology, 2015)
Information and Communication Technologies (ICTs) playing a pivotal role in the development process. ICTs have a significant footprint in global resource consumption, Greenhouse Gas (GHG) emissions and waste, particularly considering the high growth rates. However, intelligent use of ICT can support other domains in mitigation monitoring of resources and environmental impacts and adaptation to unavoidable changes, for instance due to climate change. This paper provides an overview on activities to reduce the direct ICT footprint and on positive indirect effects in other domains. Finally, it briefly outlines the potential of ICT to support education, public awareness and policy-making.